2023
DOI: 10.3847/1538-4357/acdfd3
|View full text |Cite
|
Sign up to set email alerts
|

A Multiwavelength Light-curve Analysis of the Classical Nova YZ Ret: An Extension of the Universal Decline Law to the Nebular Phase

Izumi Hachisu,
Mariko Kato

Abstract: YZ Ret is the first X-ray flash detected classical nova, and is also observed in optical, X-ray, and gamma-ray. We propose a comprehensive model that explains the observational properties. The white dwarf mass is determined to be ∼1.33 M ☉, which reproduces the multiwavelength light curves of YZ Ret, from optical, X-ray, to gamma-ray. We show that a shock is naturally generated far outside the photosphere because winds collide with themselves. The derived lifetime of the shock explains some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Such a large variety in wavelengths (or energies) of emissions indicates that various emissions originate from different places or times of the nova ejecta. Hachisu & Kato (2022) and Hachisu & Kato (2023) proposed nova ejecta evolution models based on the fully selfconsistent nova outburst model of Kato et al (2022a). The authors found that a strong shock naturally arises in nova ejecta far outside the WD photosphere without ad hoc or arbitrary settings on the nova ejecta, and elucidated the origin of nova absorption/emission line systems raised by McLaughlin (1942).…”
Section: Shock Formationmentioning
confidence: 99%
See 4 more Smart Citations
“…Such a large variety in wavelengths (or energies) of emissions indicates that various emissions originate from different places or times of the nova ejecta. Hachisu & Kato (2022) and Hachisu & Kato (2023) proposed nova ejecta evolution models based on the fully selfconsistent nova outburst model of Kato et al (2022a). The authors found that a strong shock naturally arises in nova ejecta far outside the WD photosphere without ad hoc or arbitrary settings on the nova ejecta, and elucidated the origin of nova absorption/emission line systems raised by McLaughlin (1942).…”
Section: Shock Formationmentioning
confidence: 99%
“…In the later phase, the shocked shell far outside the photosphere begins to contribute to the V-band flux. Hachisu & Kato (2023) estimated the luminosity of free-free emission from the shocked shell as…”
Section: Emission From the Shocked Shellmentioning
confidence: 99%
See 3 more Smart Citations